2017
DOI: 10.1016/j.nicl.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI vs. navigated TMS to optimize M1 seed volume delineation for DTI tractography. A prospective study in patients with brain tumours adjacent to the corticospinal tract

Abstract: BackgroundDTI-based tractography is an increasingly important tool for planning brain surgery in patients suffering from brain tumours. However, there is an ongoing debate which tracking approaches yield the most valid results. Especially the use of functional localizer data such as navigated transcranial magnetic stimulation (nTMS) or functional magnetic resonance imaging (fMRI) seem to improve fibre tracking data in conditions where anatomical landmarks are less informative due to tumour-induced distortions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 114 publications
1
23
0
1
Order By: Relevance
“…In the past, several studies have shown that ROI seeding based on nTMS data resulted not only in more specific tracts with less aberrant fibers, but reduced the variability between examiners compared to the seeding approach using anatomical landmarks (Frey et al, 2012;Krieg et al, 2012;Weiss Lucas et al, 2017). In order to improve the threshold selection, previous standardization attempts suggested a FL threshold of 110 mm and the implementation of a 100%-FAT criterium.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the past, several studies have shown that ROI seeding based on nTMS data resulted not only in more specific tracts with less aberrant fibers, but reduced the variability between examiners compared to the seeding approach using anatomical landmarks (Frey et al, 2012;Krieg et al, 2012;Weiss Lucas et al, 2017). In order to improve the threshold selection, previous standardization attempts suggested a FL threshold of 110 mm and the implementation of a 100%-FAT criterium.…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve the threshold selection, previous standardization attempts suggested a FL threshold of 110 mm and the implementation of a 100%-FAT criterium. The latter described the FA threshold at which only a thin fiber tract was visualized and all other FA values were described in relation to this 100%-FAT value as e.g., 75%-, 50%-or 25%-FAT (Frey et al, 2012;Weiss et al, 2015;Rosenstock et al, 2017;Weiss Lucas et al, 2017). The concept of performing fiber tracking with a FL threshold of 110 mm and a 75%-FAT resulted in a more objective tractography than the previous methods (Frey et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations